Insecticidal constituents from the Argentine Liverwort Plagiochila bursata - Ramirez, Marta Inés (2010)
The new 2,3-secoaromadendrane 1, together with the known compounds plagiochilines A and M (2 and 3, resp.), fusicogigantone A (4), and 1,4-dimethylazulene (5) were isolated from an Argentine collection of the liverwort Plagiochila bursata. Structures were elucidated by extensive 1D- and 2D-NMR studies. Compounds 2 and 4, incorporated to the larval diet at 100 mg per g of diet, reduced the larval growth of Spodoptera frugiperda (Lepidoptera: Noctuidae) by 66±29% and 25±8% and produced 55 and 75% larval mortality at early instars and 20 and 25% pupal mortality, respectively. Treatment with compound 2 also produced abdomen and wing malformation in adults leading to impossibility to mate.